Competency Framework for the Property Management Industry - Baharum, Zarita Ahmad; Hwa, Ting Kien; Salleh, Sharuzaman Mohd (Environment-Behaviour Proceedings Journal, 2016)
Property management is a very complex and challenging profession due to its nature and coverage of work in managing not just the four walls but what inside and outside the four walls. In addition, the task also requires monitoring of 24/7 and 365 days. The team of property management consists of various backgrounds to ensure that it can cater the needs and requirements of each building. Thus, to deliver quality services would require a minimum competency according to their scope and area of work. This research is aim to develop the property management competency framework that is applicable in the Malaysian property management service delivery. The method used is using focus group consists of the experts in the industry either private organizations or public institutions; nationally and internationally. Findings reveal that the knowledge base and technical skills required of today’s property management professional have changed significantly. The competency requirements for a professional property manager include advanced technical knowledge, a good grasp of business operations and a working knowledge of the real estate business environment. The ability to integrate different business concepts, apply sustainability principles, to be cost effective and a strong ethical foundation is an essential element of a successful professional property manager. Hence, it is crucial to have the minimum competency level as a basis to deliver excellent quality service as well as to be adapted and adaptable to the environment, the stakeholders and the buildings. Â© 2016. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. Keywords: Property management, competency framework, property management industry